Plant polysaccharides with anti-lung injury effects as a potential therapeutic strategy for COVID-19 - Huang, Peng; Zhang, Jiahui; Duan, Wenqian; Jiao, Juying; Leng, Aijing; Qu, Jialin (Frontiers in Pharmacology, 2022)
When coronavirus disease 2019 (COVID-19) develops into the severe phase, lung injury, acute respiratory distress syndrome, and/or respiratory failure could develop within a few days. As a result of pulmonary tissue injury, pathomorphological changes usually present endothelial dysfunction, inflammatory cell infiltration of the lung interstitium, defective gas exchange, and wall leakage. Consequently, COVID-19 may progress to tremendous lung injury, ongoing lung failure, and death. Exploring the treatment drugs has important implications. Recently, the application of traditional Chinese medicine had better performance in reducing fatalities, relieving symptoms, and curtailing hospitalization. Through constant research and study, plant polysaccharides may emerge as a crucial resource against lung injury with high potency and low side effects. However, the absence of a comprehensive understanding of lung-protective mechanisms impedes further investigation of polysaccharides. In the present article, a comprehensive review of research into plant polysaccharides in the past 5 years was performed. In total, 30 types of polysaccharides from 19 kinds of plants have shown lung-protective effects through the pathological processes of inflammation, oxidative stress, apoptosis, autophagy, epithelial–mesenchymal transition, and immunomodulation by mediating mucin and aquaporins, macrophage, endoplasmic reticulum stress, neutrophil, TGF-β1 pathways, Nrf2 pathway, and other mechanisms. Moreover, the deficiencies of the current studies and the future research direction are also tentatively discussed. This research provides a comprehensive perspective for better understanding the mechanism and development of polysaccharides against lung injury for the treatment of COVID-19.